1990
DOI: 10.7164/antibiotics.43.587
|View full text |Cite
|
Sign up to set email alerts
|

A54145, a new lipopeptide antibiotic complex. Discovery, taxonomy, fermentation and HPLC.

Abstract: A54145is a complex of new lipopeptide antibiotics that inhibits Gram-positive bacteria and acts as a growth promotant for broiler chicks. Eight factors; A, B, C, D, E, F, At and B^have been isolated and characterized. They contain four similar peptide nuclei, each of which is acylated with either an 2-decanoyl, rc-decanoyl, or undecanoyl side chain. Taxonomicstudies ascertained that the producing microorganism was a strain of Streptomyces fradiae. Fermentation studies determined that superior antibiotic yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 6 publications
1
44
0
Order By: Relevance
“…In addition, the identification of the acyl group was further confirmed by observing a homogeneous peak at t R 7.01 min after spiking the reaction resultant of 1 with the library mixture ( Figure 3c). As a result, the anteiso-undecanoyl (aC 11 ) group was identified in 1, as expected from fermentation of S. fradiae DA1489 in DSF medium supplemented with L-Ile. 14, 18 Structural characterization of 1 by NMR studies was somewhat challenging because of the observation of two sets of 1 H-NMR signals in DMSO-d 6 .…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…In addition, the identification of the acyl group was further confirmed by observing a homogeneous peak at t R 7.01 min after spiking the reaction resultant of 1 with the library mixture ( Figure 3c). As a result, the anteiso-undecanoyl (aC 11 ) group was identified in 1, as expected from fermentation of S. fradiae DA1489 in DSF medium supplemented with L-Ile. 14, 18 Structural characterization of 1 by NMR studies was somewhat challenging because of the observation of two sets of 1 H-NMR signals in DMSO-d 6 .…”
Section: Introductionsupporting
confidence: 54%
“…9,10 A54145 is a family of cyclic tridecapeptide antibiotics related to daptomycin and produced by Streptomyces fradiae. [11][12][13][14][15] The A54145 lipopeptides contain several nonproteinogenic amino acids, including hydroxyasparagine (hAsn 3 ), sarcosine (Sar 5 ), methoxyaspartic acid (moAsp 9 ) and 3-methylglutamic acid (3mGlu 12 ). 12 Four different cyclic peptide nuclei vary in the ring amino acid residues Glu/3mGlu at position 12 and Ile/Val at position 13.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, A54145 factors containing Glu 12 accumulate early in fermentation and those containing 3mGlu 12 accumulate later, with final yields of about 60% of factors containing Glu 12 . 1 The study by Boeck et al 5 demonstrated that the distribution of A54145 factors can be manipulated by adding certain amino acids or lipids to the fermentation. For instance, feeding L-Ile, enriched for factors containing Ile 13 from 89 to 98%, whereas feeding L-Val (which inhibited overall lipopeptide production by about 70%) enriched for compounds containing Val 13 from 11 to 56%, almost exclusively in…”
mentioning
confidence: 99%